Unified Parametrization of Phonetic Features and Numerical Calculation of Phonetic Distances between Speech Sounds. Issue 1 (2nd January 2023) - Vakulenko, Maksym O.
ABSTRACT: A metric method to numerically measure phonetic and phonemic distances or contrasts, between speech sounds, is put forward. The feature values of the compared phones taken from the standard IPA charts are treated as independent parameters that give rise to corresponding Euclidean distances. As an illustration, the general phone set is mapped to Ukrainian phonemes. The proposed model agrees well with the historical linguistic facts and experimental phonetic data. The described approach may find its due applications in various fields of linguistics and speech technologies, including historical and typological linguistics, language acquisition, phonetic studies, computational phonology, machine translation, information retrieval, and text-to-speech conversion.